Echocardiography findings in COVID-19 patients admitted to intensive care units: a multi-national observational study (the ECHO-COVID study) - Huang, Stephen; Vignon, Philippe; Mekontso-Dessap, Armand; Tran, Ségolène; Prat, Gwenael; Chew, Michelle; Balik, Martin; Sanfilippo, Filippo; Banauch, Gisele; Clau-Terre, Fernando; Morelli, Andrea; De Backer, Daniel; et al. (Intensive care medicine, 2022)
PURPOSE: Severely ill patients affected by coronavirus disease 2019 (COVID-19) develop circulatory failure. We aimed to report patterns of left and right ventricular dysfunction in the first echocardiography following admission to intensive care unit (ICU). METHODS: Retrospective, descriptive study that collected echocardiographic and clinical information from severely ill COVID-19 patients admitted to 14 ICUs in 8 countries. Patients admitted to ICU who received at least one echocardiography between 1st February 2020 and 30th June 2021 were included. Clinical and echocardiographic data were uploaded using a secured web-based electronic database (REDCap). RESULTS: Six hundred and seventy-seven patients were included and the first echo was performed 2 [1, 4] days after ICU admission. The median age was 65 [56, 73] years, and 71% were male. Left ventricle (LV) and/or right ventricle (RV) systolic dysfunction were found in 234 (34.5%) patients. 149 (22%) patients had LV systolic dysfunction (with or without RV dysfunction) without LV dilatation and no elevation in filling pressure. 152 (22.5%) had RV systolic dysfunction. In 517 patients with information on both paradoxical septal motion and quantitative RV size, 90 (17.4%) had acute cor pulmonale (ACP). ACP was associated with mechanical ventilation (OR > 4), pulmonary embolism (OR > 5) and increased PaCO2. Exploratory analyses showed that patients with ACP and older age were more likely to die in hospital (including ICU). CONCLUSION: Almost one-third of this cohort of critically ill COVID-19 patients exhibited abnormal LV and/or RV systolic function in their first echocardiography assessment. While LV systolic dysfunction appears similar to septic cardiomyopathy, RV systolic dysfunction was related to pressure overload due to positive pressure ventilation, hypercapnia and pulmonary embolism. ACP and age seemed to be associated with mortality in this cohort.
Keywords: Ventricular Dysfunction, Right; Humans; Heart Failure; srdeční selhání; echokardiografie; Echocardiography; Female; Aged; senioři; lidé; Hypertension, Pulmonary; plicní embolie; dysfunkce pravé srdeční komory; Pulmonary Embolism; COVID-19; plicní hypertenze; ženské pohlaví; Male; jednotky intenzivní péče; Retrospective Studies; dysfunkce levé srdeční komory; Ventricular Dysfunction, Left; retrospektivní studie; Intensive Care Units; mužské pohlaví